CONCEPTUAL STUDY ON FACTOR AFFECTING GREEN PURCHASING BEHAVIOR - Nur Faithzah Binti Jamian; Nurfazilla Binti Jefrry; Afdlin Irfan Din Bin Saruddin; Nur Hidayah Binti Mohd Sapei; Muhammad Asyraf Bin Aimilan; Mohammad Faizul Naim Bin Ahmad; Wan Shahrul Aiman Bin Wan Muhammad Zaki (International Journal of Accounting, Finance and Business, 2022)
In reducing the impacts of environmental issues, green purchasing has become an alternative among consumers in Malaysia. The green purchasing or ecolabel product is a type of positive statement identifying a specific product or service as being less harmful to the environment than other similar products or services. Several types of environmental damage result from product materials where the manufacturing processes should be minimized. Hence, by purchasing green items, consumers can help to prevent or lessen environmental damage. In Malaysia, consumers have shown a high level of environmental awareness but display moderate outcomes in purchasing green products. Thus, this paper aims at presenting the reviews of the literature on the factors influence on purchasing green products by consumers. From the studies ranging from the year 2012 to 2022, many factors have been identified toward green purchasing such as consumer’s environmental concerns, green labelling, quality of the green product, and green purchasing intention. The review will give a holistic understanding on the factors influencing green purchasing for future researchers and aid to identify the research gap.